Unformatted text preview: 10^9 G 10^6 M 10^3 k 10^2 c 10^3 m 10^6 μ 10^9 n 10^12 p ρ= m v d ε V ≡ lim
ε →0 V ≡ lim ∆x dx = ε → 0 ∆t dt d C =0 dx d x =1 dx dn x = nx n −1 dx d ax n = a ⋅ nx n −1 dx d 1 d −1 1 = x = −1x −1−1 = − 2 dx x dx x d sin ( 3θ ) = 3 ⋅ cos( 3θ ) dx d cos(2θ ) = −2 sin(+θ ) Vi 2 V f dx V= 2 1 x = at 2 2 σ= ∑ (x 1 − x) 2 n −1 ∆ρ ∆m ∆v = + ρ m v ∆v a ≡ lim ∆t →0 ∆t V = f ′( x), a = f ′′( x) ∆x = x f − xi V = at 1 x f − xi = vi ⋅ t + ⋅ a ⋅ t 2 2
V f = Vi + at v 2 = v 2 − 2 ⋅ a ⋅ ( x − x ) f i f i ...
View
Full
Document
This note was uploaded on 03/12/2010 for the course PHY 110 taught by Professor Su during the Fall '08 term at Illinois State.
 Fall '08
 SU
 Physics

Click to edit the document details